The Relationship between Masticatory Performance and Dental Caries Status in 4-Year-Old Children - Ganbaatar, Nomin; Bazar, Oyuntsetseg; Altansukh, Suvdanchimeg; Bayarmagnai, Namuun; Okazaki, Yoshihide (Central Asian Journal of Medical Sciences, 2019)
Objectives: Our study aimed to evaluate the relationship between masticatory performance and dental caries in 4-year-old children. Methods: A total of 100 4-year-old children of both genders were selected from 3 kindergartens. The data collected included the masticatory performance test, oral examination and sociodemographic data including aspects of their dental care and eating habits. Masticatory performance was assessed using chewing gum. Participants chewed a piece of gum for 3 minutes and then it was weighed, recognizing that during mastication the soluble part of the gum dissolves reducing its weight. The results were compared among the participants examining the potential factors affecting mastication. Results: The mean the number of decayed filled teeth was 3.8 teeth. Chewed gum mean weight was 0.57 g ±0.49 (boys vs. girls, 0.58±0.03 vs. 0.57±0.05 g, NS). There was a positive correlation between gum weight and decayed teeth (r=.57, p<.0001). Linear regression showed that gum weight increased by 0.005 g for every decayed tooth (p<.0001). Conclusion: A significant positive correlation was observed between masticatory performance and the number of decayed teeth. Our linear regression results clearly showed that number of decayed teeth was associated with decreased masticatory performance as accessed by our gum weighing method.